2002
DOI: 10.1007/s002110100274
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale finite element for problems with highly oscillatory coefficients

Abstract: In this paper, we study a multiscale finite element method for solving a class of elliptic problems with finite number of well separated scales. The method is designed to efficiently capture the large scale behavior of the solution without resolving all small scale features. This is accomplished by constructing the multiscale finite element base functions that are adaptive to the local property of the differential operator. The construction of the base functions is fully decoupled from element to element; thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…In a stochastic system, our former analysis showed that a very high coarsening level will lead to the overestimation of the head variance (Shi et al, 2010). (2) The boundary condition for solving the coarse-scale basis functions has significant effect on the multiscale simulation in the heterogeneous media (Efendiev and Wu, 2001). The oscillatory boundary condition produces much smaller error than the linear boundary condition.…”
Section: Reconstruction Of Fine-scale Solutionmentioning
confidence: 98%
“…In a stochastic system, our former analysis showed that a very high coarsening level will lead to the overestimation of the head variance (Shi et al, 2010). (2) The boundary condition for solving the coarse-scale basis functions has significant effect on the multiscale simulation in the heterogeneous media (Efendiev and Wu, 2001). The oscillatory boundary condition produces much smaller error than the linear boundary condition.…”
Section: Reconstruction Of Fine-scale Solutionmentioning
confidence: 98%
“…For analysis, we introduce the following spaces: For any T ⊂ , with the norm (see [12] and [11]) Here < ·, · > e is the duality pairing. Although for functions in S h (T) the flux jump condition is enforced on line segments DE, they actually satisfy a weak flux jump condition on the interface .…”
Section: Approximation Property Of the Immersed Interface Space S H (T)mentioning
confidence: 99%
“…The elliptic flux a (x, ξ) satisfies the same assumptions, (5) and (6), imposed in the previous section. We denote the differential operator corresponding to (8) by A . It is known that (e.g., [16, p. 90…”
Section: Numerical Homogenizationmentioning
confidence: 99%
“…In the previous findings, MsFEM (see [10,9,7,8]) and other upscaling techniques (see, e.g., [21,5,2]) have been successfully applied to linear elliptic equations. In this case the coarse scale solution can be constructed by rescaling of the local solution or the coupling of the local solution through the variational formulation of the problem.…”
mentioning
confidence: 99%